PENGARUH LINGKUNGAN TERHADAP PERILAKU AGRESIF VERBAL SISWA DALAM BERKOMUNIKASI - Agung Prasetya; Fauzi, Taty; Ramadhani, Erfan (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2019)
Verbal aggressive behavior is a negative behavior that is often found in everyday life. Researchers found verbal forms of student behavior when communicating with friends such as taunting friends by mentioning the name of a parent, hurting a friend by calling him an illegitimate child, and speaking harshly to the teacher. This study aims to determine whether there is an influence of the school environment on students' verbal aggressive behavior in communication. The population of this research is VIII grade students. The research sample of 160 people were selected using the Stratified Random Sampling technique. Data analysis using correlational product moment with the results of r_count of 0.328 and r_tabel value of 0.148 or in other words r_count> r_tabel = 0.328> 0.148. This shows the influence of the school environment on students' verbal aggressive behavior in communication.